A Novel Small Animal Model of Differential Anterior Cruciate Ligament Reconstruction Graft Strain - Ma, Richard; Ju, Xiaodong; Deng, Xiang-Hua; Rodeo, Scott A. (The Journal of Knee Surgery, 2015)
The aim of the study was to establish a small animal research model of anterior cruciate ligament (ACL) reconstruction where ACL graft force can be predictably altered with knee motion. Cadaveric rat knees (n = 12) underwent ACL resection followed by reconstruction. Six knees received anterior (high-tension) femoral graft tunnels and six knees received posterior (isometric) graft tunnels. All the 12 knees and ACL grafts were pretensioned to 3 N at 15 or 45 degrees of knee flexion. ACL graft force (N) was recorded as the knee was ranged from extension to 90-degree flexion. Distinct ACL graft force patterns were generated for a high-tension and isometric femoral graft tunnels. For a high-tension femoral tunnel, the rat ACL graft remained relatively isometric at lower knee flexion angles but increased as the knee was flexed beyond 45 degrees. At 90 degrees, high-tension grafts had significantly greater mean graft tension for both pretensioning at 15 degrees (5.58 ± 1.34 N, p = 0.005) and 45 degrees (6.35 ± 1.24 N, p = 0.001). In contrast, the graft forces for isometric ACL grafts remained relatively constant with knee flexion. Compared with a high-tension ACL grafts, the graft force for grafts placed in an isometric tunnel had significantly lower ACL graft forces at 60, 75, and 90 degrees of knee flexion for both pretensioning at 15 and 45 degrees, respectively. We were able to demonstrate that ACL graft forces in our rat model of ACL reconstruction were sensitive to femoral tunnel position similar to human knees. We were also able to establish two reproducible femoral graft tunnel positions in this small animal model, which yielded significantly different ACL graft tension patterns with knee range of motion. This model would permit further research on how ACL graft tension may affect graft healing.
Keywords: ACL graft strain; ACL isometry; ACL tunnel position